Search Computing Trends and Developments - Ceri, Stefano; Brambilla, Marco; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Search computing, which has evolved from service computing, focuses on building the answers to complex search queries by interacting with a constellation of cooperating search services, using ranking and joining of results as the dominant factors for service composition. The field is multi-disciplinary in nature, and takes advantage of contributions from other research areas such as knowledge representation, human-computer interfaces, psychology, sociology, economics and legal sciences. This second Search Computing book is divided into eight parts focusing on the search process, interaction design, semantic description, rank join, query processing, tools and mashups, bio-seco, and sustainable exploitation reflecting the many research directions of the Search Computing project (SeCo).
The Search Process:- The New Frontier of Web Search Technology: Seven Challenges -- Information Exploration in Search Computing -- Trends in Search Interaction -- Interaction Design:- Context and Action in Search Interfaces -- Desktop, Tabletop or Mobile? -- Visualization of Multi-domain Ranked Data -- Semantic Description:- Semantic Resource Framework -- Automatic Normalization and Annotation for Discovering Semantic Mappings -- Towards an Ontological Representation of Services in Search Computing -- Rank Join:- The Rank Join Problem -- Proximity Rank Join in Search Computing -- Uncertainty in Rank Join -- Trends in Rank Join -- Query Processing:- Efficient Computation of Search Computing Queries -- Run-Time Adaptivity for Search Computing -- Tools and Mashups:- Tools Supporting Search Computing Application Development -- Distributed User Interface Orchestration: On the Composition of Multi-User (Search) Applications -- On Development Practices for End Users -- Bio-SeCo:- Bio-SeCo: Integration and Global Ranking of Biomedical Search Results -- Workflows for Information Integration in the Life Sciences -- Complex Search, Ranks, and Biological Discovery: A User?s Perspective -- Towards a Sustainable Exploitation:- An Experience in Applying User Centered Design to Search Computing -- Analysis of Business Models for Search Computing.
Electronic reproduction.
Keywords: Electronic information resource searching -- Congresses